EVALUASI ASPEK FUNGSI TANAMAN PADA LANSKAP JALAN KAMPUS UNIVERSITAS SAM RATULANGI - Arief Rahman; Jemmy Najoan; Maria G.M. Polii (COCOS, 2015)
ABSTRACT EVALUATION OF PLANT FUNCTIONAL ASPECT AT SAM RATULANGI UNIVERSITY ROADSIDE LANDSCAPE   Plant is one of the elements that play a role in shaping the roadside landscape. The aim of this study was to evaluate aspects of the functioning of plants in the landscape of the campus of the University of Sam Ratulangi and make recommendations on the selection and arrangement of functional plants. The experiment was conducted from April to November 2015 along the roadside of the University of Sam Ratulangi.      This is a descriptive study, data collection is collect by survey method. Location of the study were divided into 4 groups of locations: Main Street, East Zone, West Zone and South Zone. Plant function evaluated is the advisory function, limiting, shade, wind control, noise control, light control, pollution control, and conservation. Each group location rated based on the percentage criterion crop function and translated into the category of excellent, good, average, and poor.      Results of the evaluation showed excellent categories are on main street group location, good categories located in east zone and west zone group’s location, and poor categories located in South Zone group location. Function of plants on the landscape the way the campus can be improved by increasing the number of trees and shrubs that has a dense leaves and planted with a tightly spacing. The selection of plants should consider the composition of the existing planting, plant function requirements, and compliance with the physical and environmental conditions of the road. . Keywords: Plant Functional, Roadside Landscape, University of Sam Ratulangi